Looking Back To A Job Well Done? Measuring Success in the Integration of Teaching and Learning across Multiple Modes of Delivery - MackIntosh, Lara; Beard, Natalie; Macedo, Joseli (2017)
Thirty years ago, in 2017 we embraced a strategy to integrate all modes of teaching delivery in the School of Built Environment at Curtin University. We knew there would be significant challenges to teaching and learning practices. Back then, face-to-face and online teaching were considered discrete and separate practices; however, this was not reflected in the learning experience of students, predominantly the original digital natives, for whom new technologies had become a necessary part of their lives. The purpose behind integrating learning modes, in addition to embracing improved digital technologies, was to improve the teaching and learning experiences by recognising successes in both face-to-face and online practices, and adapting to suit all modes. All stakeholders had to participate, engage and commit to adapting teaching and learning practices to the new digital environments. This paper addresses what was a complex problem from the point of view of the different stakeholders— institutions, staff and students. The similarities and gaps in the support provided are discussed with the aim to identify alternative ways of supporting success in teaching and learning. This paper discusses the support offered in transitioning into the digital age and implementing an integrated strategy of delivery. In 2017 when this project was initiated, it had already become clear that the stage was set for further research on this topic. Since 2017 the work discussed in this paper was used to build the limited data available to develop tools that could be employed to measure the success of this strategy.